Handwriting of the twentieth century - Sassoon, Rosemary (Intellect, 2007)
The history of formal calligraphy has been thoroughly documented, and the demise of what people see as beautiful handwriting is frequently deplored, but the details of the teaching of this skill during this century have gone almost unrecorded. Everyday handwriting is ephemeral and school books soon disappear. The main purpose of this book is to create a historical record, however, techniques are illustrated that may be useful for teachers today, while the ever-changing views of the stylists provide examples, as well as a warning, to those who plan for the future. An individual sample of handwr.